Employment and the Financial Crisis: Evidence from Tajikistan - Antje Kröger; Kristina Meier (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
The financial crisis in 2008/2009 had a presumably substantial influence on the everyday social and economic life of many Tajik people, including their behavior in the labor market. In our paper, we aim to study the impact of the economic crisis on individual labor market decisions. This is the first study investigating the impact of the financial crisis in a transition country using a unique panel data set from Tajikistan. We find that the global financial crisis had a strong impact on employment and migration patterns in Tajikistan. Our results show that regular wage employment and self-employment with hired labor decreased while piece-based wage employment and unpaid family work increased during the crisis. Further, households are more likely to send a family member abroad suggesting that the dependency on sending migrants abroad grows in times of economic turmoil. In combination with increased migration risk our results show that the Tajik labor market has largely been affected by the global financial crisis.
Keywords: C23; J24; J16; O10; 330; financial crisis; wage employment; migration; Tajikistan